Analisis Bias Gender Pada Soal Ujian Bahasa Arab di Madrasah Tsanawiyah - Sholikah Mi'rotin; Mufidah Cholil (Institut Agama Islam Negeri (IAIN) Metro, 2020)
Gender analysis is not only to determine the equality of public roles between men and women in conversational texts, reading texts in textbooks, but gender analysis can also be carried out on questions used by teachers to evaluate students. For this reason, the author will carry out a gender analysis on the school examination items in Arabic learning which are used to determine student graduation. This study aims to determine the number of questions contained in the gender variant, and whether the school exam questions presented are gender-biased. So that it can be used as evaluation material and can reconstruct evaluations that contain gender bias to become more gender responsive. This research uses a qualitative approach to library research. Data collection techniques using interviews, questionnaires, and documentation. The data analysis technique was carried out in three stages, namely data collection, data presentation and drawing conclusions. The results of the research were: 1) questions containing gender equality consisted of 4 questions, gender neutral consisted of 30 questions, and gender bias consisted of 16 questions. 2) less than half of the school exam questions are gender bias oriented with a percentage of 32%.